Application of natural and artificial fallout radionuclides to determining sedimentation rates in New Zealand lakes - N. E. Whitehead; R. G. Ditchburn; W. J. McCabe; W. J. Mason; J. Irwin; R. A. Pickrill; G. R. Fish (New Zealand Journal of Marine and Freshwater Research, 1998)
Sedimentation rates have been estimated for New Zealand Lakes Rotoiti, Taupo, Ngahewa, Tikitapu, Okareka, Pukaki, Rotorua, Waikaremoana, Wakatipu, Tekapo, and Ohau, and also the Falls Dam, Central Otago, the Pauatahanui inlet (Wellington), and Lake Vanda (Antarctica). Sedimentation rates were able to be calculated using the 210 Pb and 210 Po methods in 26 out of 28 cores. For the 137 Cs method (shown equivalent to the previous methods) calculable rates were obtained in 13 out of 19 cores. An age estimation was always possible by one of the methods. Values of 147 Pm and 144 Ce showed that most surface layers were undisturbed, hence the hypothetical mixing often invoked to explain 137 Cs profiles lacking the expected 1965 peak is incorrect for most of these cores. Deficits in surface layer 210 Pb caused by 222 Rn loss did not affect the estimates of sedimentation rate. One core contained a record dated back to 1800 A.D. Deposition rates of 210 Pb depended on rainfall, not river input. Some local geothermal activity emits 222 Rn and deposits more 210 Pb than usual for New Zealand lakes, but otherwise absolute 210 Pb levels are generally very low compared to other studies. Deposition rates varied from a low of 0.11 kg m‐ 2 yr‐1 (Lake Tikitapu) to a high of 28 kg m‐ 2 yr‐ 1 (one Lake Pukaki core).